THE MAIN WAYS TO INTRODUCE DIGITAL TECHNOLOGIES IN EDUCATION (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2025)
This article examines the main pathways of implementing digital technologies in education, analyzing current trends, challenges, and opportunities. The research focuses on theoretical frameworks and literature analysis to identify effective strategies for digital transformation in educational settings.
Keywords: digital education; e-learning; educational technology; digital transformation; teaching methods; educational innovation